2014
DOI: 10.1016/j.cmet.2014.07.008
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Grizzly Bears Exhibit Augmented Insulin Sensitivity while Obese Prior to a Reversible Insulin Resistance during Hibernation

Abstract: The confluence of obesity and diabetes as a worldwide epidemic necessitates the discovery of new therapies. Success in this endeavor requires translatable preclinical studies, which traditionally employ rodent models. As an alternative approach, we explored hibernation where obesity is a natural adaptation to survive months of fasting. Here we report that grizzly bears exhibit seasonal tripartite insulin responsiveness such that obese animals augment insulin sensitivity but only weeks later enter hibernation-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…97). Recent data show that hibernating grizzly bears respond to insulin in the spring and autumn, but not during the hibernation season (207). Clearly, this is a fruitful area for future research.…”
Section: Food Quantity and Qualitymentioning
confidence: 99%
“…97). Recent data show that hibernating grizzly bears respond to insulin in the spring and autumn, but not during the hibernation season (207). Clearly, this is a fruitful area for future research.…”
Section: Food Quantity and Qualitymentioning
confidence: 99%
“…One condition in which specifi c organisms are challenged with prolonged fasting is hibernation. A recent study has demonstrated that during hibernation, grizzly bears exhibit reversible insulin resistance coupled with elevated lipolysis and markedly increased aP2 expression, and their glucose levels are well maintained at this stage ( 60 ). In the posthibernation period when bears are no longer reliant on fat stores, adipose aP2 levels are dramatically decreased and insulin sensitivity is increased.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Similarly humans with haplo-insufficiency due to mutations in PTEN were found to have enhanced insulin sensitivity [48]. Recently an increase in insulin sensitivity due to suppression of PTEN has been described in grizzly bears in preparation for hibernation, indicating that this is a mechanism for physiological adaptation [49].…”
Section: Phosphatase and Tensin Homolog (Pten)mentioning
confidence: 99%